Who writes the news? Authorship and gender representation in press coverage of the 2014 referendum on Scottish Independence. Issue 1 (February 2020) - Patrick, David
Abstract : This paper engages with newspaper coverage of the 2014 Scottish independence referendum, with the primary focus being authorship of news and comment articles. Taking a predominantly quantitative approach, weekday coverage during August and September 2014 from eight major newspapers in Scotland was statistically analysed. The findings reveal several notable observations. First, it is observed that a large proportion of articles are published without an attributable author. Second, the findings reveal that both news and comment outputs in 2014 were dominated by a comparatively small number of individual journalists. Whilst the journalistic pool from this sample featured several hundred distinct journalists, more than half of all coverage was concentrated within the hands of only a few dozen people. Third, and most developed in this paper, is the consistent trend – across several variables – that women were marginalised within the news production process surrounding the 2014 referendum. With only a few exceptions, both news reporting and comment (including opinion, diaries and features) were dominated by male reporters; meaning that during a hugely important period of Scotland's political history, female voices and perspectives were regularly missing from the press coverage of what was seen by many as an unprecedented national conversation.